Modern Foreign Popular Music As a Means of Teaching An English Language to Students of A Non-Linguistic Profile - Komila Rishatovna, Babaeva; Gulnoza Utkurovna, Istamova; Zilola Habibullaevna, Abidova; Ziyoda Maratovna, Khudayarova; Dilshoda Kakhramonovna, Maksudova (International Journal of Psychosocial Rehabilitation, 2020)
The article discusses contemporary foreign popular music as a means of teaching English to students of non-linguistic profile. The author reveals its methodological potential and substantiates the effectiveness of its use in the classroom with university students.